28 Probability of coronary disease and clinical outcomes in patients with type 2 myocardial infarction. (17th July 2020) - Wereski, Ryan; Hung, John; Shah, Anoop SV; Anand, Atul; Strachan, Fiona E; Mills, Nicholas L; Chapman, Andrew R
Abstract : Background: Type 2 myocardial infarction is common in clinical practice. However, despite these patients having a similar rate of major adverse cardiovascular events as those with atherothrombotic type 1 myocardial infarction, there is currently no consensus on how these patients should be evaluated or managed. Whether risk assessment for coronary artery disease can identify patients at increased risk of death is unclear. Methods: The High-STEACS trial was a stepped wedge cluster randomised controlled trial in ten hospitals across Scotland, including 48, 282 consecutive patients with suspected acute coronary syndrome. The index diagnosis was adjudicated in all patients and the likelihood of underlying coronary artery disease recorded as either low probability, high-probability, or known based on the clinical history, risk factors and comorbidities. The adjudicators were blinded to the primary and secondary outcomes including all-cause mortality at one year. Results: High-sensitivity cardiac troponin I concentrations were above the sex-specific 99th centile in 22% (10, 360/48, 282) of patients. The adjudicated diagnosis was type 1 and type 2 myocardial infarction in 55% (4, 981/9, 115) and 12% (1, 121/9, 115), respectively. Compared to patients with type 1 myocardial infarction, those with type 2 myocardial infarction were older and more likely to be women. In patients with type 2 myocardial infarction, 20% were low-probability, 55% were high-probability and 25% had known coronary artery disease. All-cause mortality was highest in patients with known or suspected coronary artery disease (22.5% and 23.3%, respectively). Those with a low-probability of coronary artery disease had the lowest event rate (8.8%), even compared to those with type 1 myocardial infarction (figure 1 ). Discussion: A simple clinical assessment of whether patients have a low- or high-probability of coronary artery disease is associated with future risk of death in patients with type 2 myocardial infarction. Whether incorporating this assessment into clinical practice to guide secondary prevention could improve outcomes requires prospective evaluation. Conflict of Interest: None